Structure and properties of the hybrid and topological transformer models. (June 2020) - Zhao, Jianhui; Zirka, Sergey E.; Moroz, Yuriy I.; Arturi, Cesare M.
Highlights: Three transformer models for low-frequency transient simulations are examined. Non topology of the hybrid transformer model is explained. Transformer models, which take into account thicknesses of transformer windings are proposed. Internal and external transformer behaviors under short circuit conditions are modeled. Abstract: Three topological transformer models for low-frequency transient simulations are considered in increasing order of their topology. It is first shown that the well-known hybrid model is not a strictly topological one, but despite this, it can be used in many applications. The next is the simplified model, which is a strict electric equivalent of the popular magnetic model, and the last is a detailed electric model, which takes into account thicknesses of transformer windings. This model improvement allows one to reproduce experimentally observed behaviors of the magnetic fluxes in the legs and yokes under short circuit conditions.